Patent Landscape for Nanotechnology - Alexey Streletskiy; Vladimir Zabavnikov; Emil Aslanov; Dmitriy Kotlov (Foresight and STI Governance, 2015)
This paper investigates the methodological aspects of nanotechnology patent landscaping. The authors suggest that nanotechnologies take precedence over other technological trends, an assertion that is confirmed by current assessments and forecasts regarding the size of the nanotechnology product market. In this paper the authors analyse patent activity within the Russian Federation and globally by building a patent map of nanotechnology and the associated field of metallurgy. Using this as a basis, a new methodological approach is posited to search for nanotechnology solutions using key words and relevant interdisciplinary terms. The practical significance of these methodological approaches is confirmed by the activities of the Fund for Infrastructure and Educational Programmes (FIEP). The FIEP helps in determining the thematic scope of newly developed educational programmes, finding potential developers working on a common intellectual and material basis for the educational process, and selecting potentially interested partner companies to ensure observance of the programmes’ structure and quality to manufacturing requirements and the needs of the labour market.